Returning to Karl Popper : a reassessment of his politics and philosophy - Naraniecki, Alexander. (Schriftenreihe zur Philosophie Karl R. Poppers und des Kritischen Rationalismus / Series in the Philosophy of Karl R. Popper and Critical Rationalism, 2014)
Over the last few years there has been a resurgent interest in various scientific disciplines in Popper's arguments. To gain a greater appreciation of Popper's scientific arguments, they need to be viewed in relation to his broader philosophy and where this stands within the history of ideas. This book aims to take seriously those aspects of Popper's writings that have received less attention and wherein he advanced metaphysical, speculative, mystical-poetic, aesthetic and Platonic arguments. Such arguments are crucial for an appreciation of his scientific and political writings. I argue that Popper, much like Wittgenstein previously has been misconstrued as an Anglo-analytic philosopher. This book provides an interpretation of Popper's mature philosophy within his Central-European intellectual context. The aim of which is to open up a fruitful line of investigation into Popper's thought that I hope would continue over the coming years.